Physicochemical Parameters and Alarming Coliform Count of the Potable Water of Eastern Himalayan State Sikkim: An Indication of Severe Fecal Contamination and Immediate Health Risk - Singh, Ashish Kumar; Das, Saurav; Singh, Samer; Pradhan, Nilu; Gajamer, Varsha Rani; Kumar, Santosh; Lepcha, Yangchen D.; Tiwari, Hare K. (Frontiers in Public Health, 2019)
Continuous decline in the potable water sources raised serious concern over human health. Developing countries are the most affected in this regard due to lack of proper hygiene maintenance. Sikkim an Eastern Himalayan state with mountains as predominant topological features harbors several perennial natural springs. Spring water is the primary source of potable water for the population in four districts of the state viz. East, West, North and South. Recent outbreaks of water-borne diseases and the relative lack of scientific studies on its potential correlation with the water quality of the area have educed this study. Physicochemical parameters of springs, community reservoir and household water were analyzed by ICP-MS and multi probe meter. Using membrane filtration method, microbial quality of the water samples during different seasons was assessed, primarily evaluating the presence of fecal indicators viz. E. coli, total coliform and Enterococcus. The seasonal risk category of the water sources was also determined. Most of the physicochemical parameters of the spring water were within the permissible limits of WHO standards. However, water from four districts was recorded with traces of toxic heavy metals viz., like mercury (0.001-0.007mg/l), lead (0.001-0.007mg/l) and selenium (0.526-0.644mg/l), which are above the permissible limits of WHO. All the spring water samples were categorized as Mg-HCO3- type and can be predicted as shallow fresh ground water based on the piper analysis. Microbial confirmatory test indicated severe fecal contamination of water sources with high counts of total coliform (TC), Escherichia coli (EC) and Enterococcus (EN). Highest TC was recorded from West Sikkim (37.26cfu/100ml) and lowest in North Sikkim (22.13cfu/100ml). Highest contamination of Escherichia coli and Enterococcus was found in East Sikkim (EC=8.7cfu/100ml; EN=2.08cfu/100ml) followed by South Sikkim (EC=8.4cfu/100ml; EN=2.05cfu/100ml). There was a significant positive correlation between the contamination level of spring water and community reservoir tank. As far as the seasonal variation is concerned, rainy season showed highest contamination with coliform correlating with high incidence of different water-borne diseases (East=86%; West=100%; South=100%; North=80%).